Study on clinical profile of scabies and comparison of efficacy of topical agents in treatment of scabies - R, Rajalakshmi; Selvaraj, Karthikeyan (Creative Pharma Assent, 2023)
Background: Scabies is an intensely pruritic mite infestation. It is a significant health problem in developing countries and remains a major issue despite available treatment modalities. Methodology: A prospective study was carried out over a year with 90 scabies patients at a tertiary care center after obtaining Ethical Clearance to study the clinical profile of scabies, compare the efficacy of various topical scabicidal agents, and evaluate improvement after treatment. After calculating the severity of pruritus and lesions, a detailed history was noted and randomly allotted to one of the treatment groups. Group A was treated with 1% GBHC lotion, Group B with 5% Permethrin cream, and Group C with 0.5% Ivermectin cream. Patients were advised to review in the second, third, and sixth weeks. Observation and results: Patients with 16-25 years of age were most susceptible. 17 out of 90 patients had secondary bacterial infections, the most common associated cutaneous disease followed by dermatophytosis. Statistically significant reduction in pruritis severity in the drug C vs drug A trial (Z = -4.810, p = <0.001) and Drug C vs drug B trial (Z= -4.795, p= <0.001). Group C (Ivermectin) causes much better improvement in itching and lesions than Group A (GBHC) and Group B (Permethrin). Conclusion: Among topicals, ivermectin can be preferred over permethrin and GBHC for treating scabies. Topical permethrin provides superior improvement when juxtaposed to GBHC and can be considered better than GBHC.